ANALISIS PENGARUH JUMLAH SUDU TURBIN PELTON TERHADAP DAYA GENERATOR PADA PROTOTYPE PEMBANGKIT LISTRIK TENAGA MIKROHIDRO - Ilhamu Dzinurain Muhandis; Basuki Basuki; Retno Eka Pramitasari; Mohammad Munib Rosadi (JURNAL ILMIAH NUSANTARA, 2024)
Micro hydropower uses water to drive a turbine which in turn rotates a generator to produce electricity. The Pelton turbine, which has bowl-shaped blades, plays a key role in capturing the water jets. This study explored the effect of the number of blades (18, 20, and 22) on the power and RPM of the micro hydropower generator through an experimental method. The results showed that the turbine with 18 blades achieved the highest power (1.19 W), while the turbine with 22 blades produced the lowest power (1.02 W). These findings confirm that the number of Pelton turbine blades significantly affects the performance of the micro hydropower, with 18 blades being the optimal choice for maximum efficiency.